Madrasah Tsanawiyah Strategy Based on Islamic Boarding Schools Implementing Religious Moderation Values in Blora Regency - Partono Partono; Ahmad Falah (Lembaga Pendidikan Hikmatun Najah Blora, 2023)
This research describes and analyzes the habituation of religious moderation values in the learning of Islamic Religious Education during the pandemic study of madrasah tsanawiyah based on Islamic boarding schools in Blora district with a research focus on how the forms, processes, and strategies of habituation of religious moderation values in PAI learning, and what are the implications for student. This research is a qualitative research using postpositivism paradigm. This type of research uses case studies, data collection uses three methods, namely: interviews, observation, and documentation. The data analysis techniques in this study used the stages of data reduction, data presentation, and drawing conclusions. The results of this study indicate that: (1) the form of habituation of the moderation value of religion in PAI learning during the pandemic during the pesantren-based madrasah studies in Blora district was carried out in the form of: through Islamic learning activities in the classroom and through religious activities. The values of religious moderation that are habituated in PAI learning are the values of justice (a'dalah), balance (tawazun), and tolerance (tasamuh). (2) The habituation process of religious moderation values in PAI learning during the pandemic during the pesantren-based madrasah tsanawiyah study in Bloradi district was carried out through: the stages of value transformation, the stages of value transactions, and the stages of value transhabituation. (3) The strategy used to habituate the value of religious moderation in Islamic Religious Education learning during the pandemic during the pesantren-based madrasah tsanawiyah study in Blora district, namely: introduction, habituation, example, and practice. (4) The implications of habituation of the value of religious moderation on the social attitudes of students during the pandemic during the Islamic boarding school-based madrasah studies in Blora district, namely being accustomed to worship, respecting teachers and friends, social care, tolerance, discipline, responsiveness to the environment, and obedience to regulations